Neo-thomism after Vatican IІ - Шиманович, А. (Київський національний університет імені Тараса Шевченка, 2023)
The article contains the author's analysis of the gradual loss of the dominant influence on Catholic theology and the educational system by the neo-Thomist intellectual project during the first decades after Vatican II. The study is primarily based on the thorough researches of such domestic and Western experts in the field of Catholic thought as A. Dakhniy, J. M. Bocheński, F. C. Copleston, G. A. McCool, F. Kerr, T. Rowland, P. D. Murray, R. J. Schreiter, B. J. Shanley and E. Lamberts. The article offers an overview of the successive rethinking of Thomism as a fixed system of ideas under the influence of postmodern relativization of generally recognized authorities, deconstruction of classical systems and concepts, and intensification the role of postmetaphysical patterns of philosophizing and theologizing. It was found out by the author that the importance of inclusiveness' strengthening within the neo-Thomist movement became possible due to the realization of the non-identity between the synthesis of St. Thomas himself and the systems that had been constructed during the period of second scholasticism (Th. Caetano, F. Suárez, D. Báñez). It is maintained that all various forms and subspecies of post-conciliar Thomistic theology are also irreducibly distinct between each other and can hardly be put together without preserving the inevitable dialectical tension between them. Such innovative term as "pluralistic complementarity", provided by Ukrainian philosopher Andriy Dakhniy, seem to be a good terminological solution for describing the possible way of overcoming the inner plurality of neo-Thomism, as well as its probable mode of existence in the context of postmodern ideological variety. The historical fact regarding the incompleteness of St. Thomas's "Summa Theologiae" – as well as K. Barth's "Church Dogmatics" – implicitly contains a hint of the potential openness of his great synthesis to the further addition and creative adaptation of Aquinas's writings in new intellectual and cultural-historical realities. In the conclusions of the article, it is substantiated that in order to maintain its own relevance in the modern ideologically pluralistic world, neo-Thomism will not be able to do without renovation processes aimed at strengthening its openness, dialogism, and ability to overcome the solidity characteristic of neo-Thomism.

Проаналізовано процес поступової втрати з боку неотомістського проєкту панівного впливу на католицьку теологію та освітню систему. В основу розвідки покладено напрацювання таких вітчизняних і західних дослідників католицької думки, як А. Дахній, Ю. Бохеньський, Ф. Коплстон, Дж. Маккул, Ф. Керр, Т. Роуленд, П. Мюррей, Р. Шрайтер, Б. Шенлі та Е. Ламбертс. Запропоновано огляд поступового переосмислення томізму як фіксованої системи ідей під впливом виник- нення постмодерністської релятивізації усталених авторитетів, деконструкції класичних систем та концепцій, а також посилення ролі постметафізичних патернів мислення. З'ясовано, що вагомість зрощення інклюзивності всередині неотомістського руху була обумовлена усвідомленням нетотожності між синтезом самого св. Томи та схоластичними системами періоду другої схоластики (Каетан, Суарес, Баньєс). Висновується, що задля збереження своєї релевантності в сучасному ідейно-плюральному світі неотомізм не зможе оминути процеси, спрямовані на зміцнення власної відкритості, діалогічності та здатності до подолання властивої неотомізмові монолітності.
Неотомізм після ІІ Ватиканського собору
Keywords: Aquinas; Middle Ages; Catholicism; Neo-Scholasticism; aggiornamento; postmodernism; Аквінат; Середньовіччя; католицизм; неосхоластика; оновлення; постмодернізм